Isolation and identification of lipolytic bacteria from galing river water kuantan to degrade waste cooking oil - Mupit, Datusahlan (2015)
Galing River is located in the center of the Kuantan city. The river was polluted by various waste and categorised as Class IV by Department of Environment. One of pollution sources is identifying came from waste cooking oil. The objective of this study is to isolate and identify of lipolytic bacteria potential, which originated from the location of the downstream Vistana hotel at the Galing River water. The ability of lipolytic bacteria in degradation of waste cooking oil is also investigated. The potential of lipolytic bacteria investigation is by using Rhodamine B. MacConKey agar is used to identify the presence of lipolytic bacteria. RapID ONE test used for the selected media, which will identify the bacteria strain name, while for a final identification is using PCR and DNA analysis. To determine the lipolytic ability of the bacteria in degrading the waste cooking oil, FTIR and gravimetric analysis are used. Most of the pollutants appear with the WQI value of 32.61. Oil and Grease value at the location M4 is 14 mg / L, while the lowest level on M1 with a value of 2 mg /L, while M2 and M3 respectively 4 mg /L and 7 mg /L. There are four bacterial strains, which had been isolated from M4 location, i.e.: Providencia stuartii, Bacillus pimilus, Exiquobacterium sp., and Bacillus antracis. The identified bacteria will be used to degrade waste cooking oil (WCO). The variation of degradation time and concentration of bacteria was observed. Measurable objective of the lipolytic bacteria capability to degrade the waste cooking oil (WCO) source in batch production based on the optical density and gravimetric data, and the rate of degradation of waste cooking oil (WCO) using FTIR. Based on that analysis, it is concluded that gravimetric analysis has a maximum value degradation of 91.39% in 100 ml variation bacteria and 4% waste cooking oil (WCO). While the minimum value of the variation of 50 μl bacteria and 1% waste cooking oil (WCO) degradation 17.08%. It’s based on a variety of media (50, 75 and 100 μl) of bacteria and 1-4% waste cooking oil (WCO). The trend increase in from 1-4% with variation bacterial of (50, 75 and 100 μl). While the degradation of waste cooking oil (WCO) using FTIR was obtained the new climax that were observed at 721 and 869 cm-1 was shown the presence of aromatic compound due to a benzene ring. FTIR provides a quick and accurate way to evaluate the structural changes from the waste cooking oil (WCO) that degraded cause by of the bacteria. As the results of this study, it can be concluded that the isolation of bacteria derived from Galing river can be used to degrade the waste cooking oil (WCO).